Skeletal Deformities in Invaded Population of Amazon Sailfin Catfish Pterygoplichthys pardalis (Castelnau, 1855) in the East Kolkata Wetland, India - Hussan, Ajmal; Sundaray, Jitendra Kumar; Ghosal, Ratna; Hoque, Farhana; Mallick, Suman (International Journal of Bio-resource and Stress Management, 2022)
The incidence of severe vertebral deformity was reported in the specimens of the Amazon sailfin catfish Pterygoplichthys pardalis (Castelnau, 1855) for the first time in India. Fish samples were collected on bimonthly basis during June 2019 to December 2020, from wastewater-fed large aquaculture impoundments (locally called ‘bheries’) of north-western part of the East Kolkata Wetlands, India. Sampling were performed using seine nets of mesh size 15 mm–30 mm and covering more or less 5,000 sq m area each time. Deformities were found in 18 specimens of Pterygoplichthys pardalis. Two types of spinal deformities, scoliosis and kyphosis, were determined visually and reconfirmed by radiography using medical X-ray system. The total length and body weights of individual fish (normal and deformed) were measured and the length-weight relationships parameters were calculated and compared. A significant difference was observed between b values of deformed (b ~1.679) and normal specimens (b>2.5) of Pterygoplichthys pardalis. Various environmental and genetic factors could contribute to the development of this deformity in the Pterygoplichthys pardalis, but based on the available data, it is impossible to confidently identify the key factor(s). However, as the fishes were from a wastewater-fed fisheries system, which receive about 600 million litres of industrial and municipal discharge of the city every day, metal and other organic contaminants could be a reason of this impairment in Pterygoplichthys pardalis.